Вечный вопрос: Какой стране принадлежит Гоголь − России или Украине? - Zarzecka, Iga (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the status of an artist’s cultural heritage in the national context on the example of Nikolaj Gogol. The author makes an attempt to answer whether Gogol’s work belongs to Russia or Ukraine by presenting the status of the particular oeuvres of the artist.